The Cinematic Canvas of Politics: A Framing Analysis of Dirty Vote Film During the 2024 Election Cycle - Dede Mercy Rolando; Tantan Hermansah; Rahmah Ningsih (Jurnal Dakwah dan Komunikasi, 2024)
This research discusses the documentary film "Dirty Vote" which successfully shocked the world of politics in Indonesia. This research is qualitative research by producing descriptive data. Researchers use Zongdan Pan & Kosicki's Framing analysis to see how the reality of the issue of fraud in the 2024 Election is structured, told, written and emphasized in the construction of a documentary film. The conclusions obtained from this research can be divided into four major structures, including: (1) Syntactic Structure, the film Dirty Vote tells about democracy which cannot be interpreted as limited to the implementation of elections and tells about power being misused; (2) The structure of the script prepared in the film Dirty Vote starts from a vote survey which shows symptoms of transactional politics, political practices of retribution, violations of integrity pacts, mass mobilization efforts in GBK, cases of corruption in village funds, intimidation of village heads, misuse and increase of budget funds. significant social assistance ahead of the election, the non-neutrality of the President and State Apparatus, Bawaslu failing to supervise the election, various KPU violations and the controversial Constitutional Court decision; (3) Thematic structure, shown in the narrative where it is stated that this victory has been planned and arranged in a structured, systematic and massive manner over the last 10 years and is controlled by power holders who can move the state apparatus and budget; (4) Rhetorical structure, Dandhy as the director wants to emphasize Jokowi's expressions which are very different from the current situation, where all his children are involved in the world of politics. However, it should be remembered that this film has no influence on the results of the 2024 presidential election recapitulation by the KPU which stated that the Prabowo – Gibran pair received the most votes in Indonesia